Real Indians : identity and the survival of Native America - Garroutte, Eva Marie, 1962- (University of California Press, 2003)
At the dawn of the twenty-first century, America finds itself on the brink of a new racial consciousness. The old, unquestioned confidence with which individuals can be classified (as embodied, for instance, in previous U.S. census categories) has been eroded.